Effectiveness of Substantive Audit Procedures on Cash and Financial Instruments: A Comparative Study of Jiwasraya and BPK Sulawesi - Deby Arachel; Azis, Nurul Latifa; Putri, Fricilya Orpi; Ita, Ita; Fadly, Muh; Asliana, Nur (Neraca Keuangan : Jurnal Ilmiah Akuntansi dan Keuangan, 2025)
This study aims to analyze the effectiveness of substantive testing in detecting fraud within cash and financial instrument accounts by comparing two audit cases Jiwasraya and BPK Sulawesi. Employing a qualitative comparative case study approach, data were obtained from audit reports, official publications, and relevant secondary sources. The findings reveal that in the Jiwasraya case, substantive testing proved less effective due to weak risk assessment of investments and inadequate fair value testing. Meanwhile, in the BPK South Sulawesi case, the low effectiveness of substantive testing was mainly attributed to the audit’s administrative focus. This study underscores the importance of enhancing professional skepticism and deepening substantive procedures to strengthen fraud detection in audit practices.